Internal exclusion as a “dumping ground”: analysis of the perspectives of parents whose children have experienced internal exclusion in UK schools - Trippler, Kiana; Anderson, Joanna; Burn, Anne-Marie (Frontiers in Education, 2025)
Internal exclusion (IE) in the UK, wherein pupils are removed from their classroom and placed in a separate area within the school, has been implemented to mixed reception with the intention of reducing classroom disruptions. For this study, an online survey was completed by 34 parents of children who have experienced IE, focusing on parent perspectives of their children’s experiences and mental health (MH), with 67% of parents reporting that their child felt distressed or unhappy while in IE. Eleven parents also participated in a semi-structured interview. Thematic analysis of interviews generated three themes: (1) IE as a tool to manage disruption, (2) counterproductive implementation, and (3) breakdown of trust with the school. Results highlight that parents felt the implementation of IE was given inappropriately, negatively impacted their child’s MH, or was ineffective in improving behaviour. Parents of pupils with learning difficulties also found IE to be difficult, and suggested alterations to existing IE implementation to support communication between schools and families and to prioritise the voices of pupils and parents in the school environment at the whole-school level.